Effect of diazepam (Valium) on dialysable thyroxine. Issue 548 (June 1971) - Saldanha, V. F.; Bird, R.; Havard, C. W. H.
Abstract : Short-term treatment with diazepam constantly reduced the level of protein-bound iodine, the percentage dialysable thyroxine and the 'free' thyroxine iodine in ten euthyroid individuals, but the serum levels remained within the normal range. The relevance of these findings to the effect of diazepam on thyroid function is discussed.